Developing techno-economically sustainable methodologies for deep desulfurization using hydrodynamic cavitation - Suryawanshi, N.B. (Fuel, 2017)
The present work, for the first time, describes the efficacy of the cavitation process and compares the cavitation yield for two types of cavitation devices-one employing linear flow for the generation of cavities and other employing vortex flow. The process involves pre-programmed mixing of the organic and aqueous phases, and can be carried out using simple mechanical cavitating devices such as orifice or vortex diode. The process essentially exploits in situ generation of oxidising agents such as hydroxyl radicals for oxidative removal of sulfur. The efficiency of the process is strongly dependent on the nature of device apart from the nature of the organic phase. The effects of process parameters and engineering designs were established for three organic solvents (n-octane, toluene, n-octanol) for model sulfur compound-Thiophene. A very high removal to the extent of 95% was demonstrated. The results were also verified using commercial diesel. The cavitation yield is significantly higher for vortex diode compared to the orifice. The process has potential to provide a green approach for desulfurization of fuels or organics without the use of catalyst or external chemicals/reagents apart from newer engineering configurations for effective implementation of hydrodynamic cavitation in industrial practice and also appears to be economically sustainable.
Keywords: Fuel; Oxidation; Petroleum; Pollution Control; Sulphur Removal

Developing spherical activated carbons from polymeric resins for removal of contaminants from aqueous and organic streams - Mane, M. B.; Bhandari, V. M. (International Journal of Environmental Science and Technology, 2022)
Spherical activated carbons from polymer resin were developed with metal modifications, before/after carbonization using copper and nickel, for gradation of zeta potential (-5.01 to 8.64 mV) and high metal loading (up to 12.3%). The materials provide improved removal of various contaminants from aqueous and organic streams-removal of bacteria from water and sulfur removal from fuel. The metal-modified spherical activated carbons were highly effective for removal of both gram-negative E. coli and gram-positive S. aureus bacteria. The copper-modified spherical activated carbon could eliminate 99.9-100%, both bacterial content proving efficacy in water disinfection with a very high rate similar to 1.33 x 10(5) (CFU/ml.s). The zeta potential has significant impact with higher disinfection for high values; similar to 10-15% disinfection can be improved up to 100% for zeta potential changes from -5 to 8.6 mV. Kinetics of disinfection was studied by accounting for zeta potential in the conventional rate model, and the efficacy of both the models was compared. The fit of revised model was excellent. The spherical activated carbons can be useful for removal of slightly polar contaminants from organic streams and a high capacity of 12.8, 20 and 28 mgS/g for thiophene, benzothiophene and dibenzothiophene, respectively. The developed materials can provide useful applications in the area of environmental pollution control. [GRAPHICS] .
Keywords: Adsorption; Material; pollution; Sulfur removal; Water disinfection